Static Retort Thermal Processing for Shelf-Life Extension of Traditional Rendang: Preliminary Study of Quality Attributes and Consumer Acceptance - Novizar Nazir; Fauzan Azima; Rendri Yasman; Aida Firdaus Nurul Azmi; Aisyah Shakira Putri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Rendang, a traditional Indonesian meat dish with significant cultural and economic value, faces distribution challenges due to its short shelf life. This study evaluated static retort thermal processing to improve rendang’s physicochemical properties, microbiological safety, and consumer acceptance. Rendang samples were sterilized at 125 °C for 0, 5, 10, 15, and 20 minutes, then analyzed for composition, Total Plate Count (TPC), and sensory properties. Sterilization affected product composition, with moisture, ash, and protein showing biphasic trends, while fat content increased steadily with increasing processing time. Microbiological analysis showed that TPC dropped from 70 CFU/g in untreated samples to 15 CFU/g or below-detectable levels (<10 CFU/g) after retort processing, confirming effective sterilization. Sensory evaluation found that all treatments maintained acceptable colour, aroma, and flavour. Consumer acceptance was high for up to six months of storage, but declined for longer shelf lives, suggesting psychological factors may influence acceptability. Overall, static retort processing at 125 °C for 10–15 minutes offers an optimal balance of safety and quality, making it suitable for extending rendang’s shelf life. Contribution of This Research to the Sustainable Development Goals (SDGs)SDG 2 – Zero Hunger.SDG 3 – Good Health and Well-being.SDG 9 – Industry, Innovation, and Infrastructure.SDG 12 – Responsible Consumption and Production.